A new species of Polyonyx Stimpson, 1858, of the P. sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) commensal with a chaetopterid worm from Peninsular Malaysia - Ng, P.K.L.; Sasekumar, A. (Naturalis, 1993)
A new species of porcellanid crab, Polyonyx vermicola, belonging to the P. sinensis group is described from Selangor, Peninsular Malaysia. The species is an obligate commensal of tubes of the chaetopterid worm Sasekumaria selangora Rullier, 1976 (Polychaeta). Polyonyx vermicola is differentiated from all congeners by its small size, possessing a more rectangular carapace, proportionately longer carpus on the larger cheliped, strongly gaping cheliped fingers, the tips of which are turned outwards, the outer surface of each cheliped fingers lined with a row of small granules, and having the ventral margin of the third ambulatory propodus armed with strong spinules.